The influence of board of commissioners’ characteristic on company carbon performance - Januarti, Indira; Juniarti, Titis Aulia Rahma (LPPM ISNJ Bengkalis, 2025)
Purpose - This study aims to analyze and empirically test the effect of the board of commissioners’ characteristics on corporate carbon performance. The variables used in this research are board size, board meetings, the presence of independent commissioners, and board gender diversity. Method - This study utilized 421 data observations from energy companies listed on the Indonesia Stock Exchange from 2018 to 2023, obtained from annual reports and sustainability reports. This study was based on these criteria: 180 samples were selected. The analytical method used is multiple linear regression analysis using SPSS version 26. Findings - The results confirmed that board meetings, independent commissioners, and board gender diversity have a positive effect on corporate carbon performance; meanwhile, board size has no positive effect on corporate carbon performance. Implications - Theoretically, in research that the improvement of corporate carbon performance is based on legitimacy and stakeholder theory. Practically, the improvement of characteristics and gender diversity present on the board of commissioners is an effort to carry out effective oversight so that business continuity is maintained by reducing carbon emissions produced.